TANGGUNG JAWAB PEMERINTAH KOTA SAMARINDA AKIBAT KERUSAKAN JALAN YANG MENYEBABKAN KECELAKAAN KENDARAAN BERMOTOR DITINJAU BERDASARKAN UNDANG – UNDANG NO. 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN - Nadia Ditasya (Universitas 17 Agustus 1945 Samarinda, 2021)
ABSTRACTTraffic accidents that occur on the road in general are always associated with errors and negligence by road riders. When in fact there are still many traffic accidents that occur due to damaged roads. The responsibility of road operators by the Government especially for road facilities is not only as if for public services but is a responsibility that was born from the Act and if not implemented can have serious legal consequences. The Government and the Regional Government in question are for the government in the administration of public roads and National roads carried out by the Minister while for the regional governments in the administration of provincial roads carried out by the Governor. So that we all know our rights and obligations are on the highway and know who is responsible for the highways that we often pass and we have financed the funds according to the taxes we pay. The road operator must immediately and properly repair damaged roads that can result in traffic accidents. The responsibility of the government as the operator of the road has a legal basis that is under the umbrella of Law Number 22 Year 2009 concerning Road Traffic and Transportation. The method used in this study uses a normative juridical approach that refers to the applicable laws and regulations. In this case, the government is obliged to provide and improve the regulation of traffic facilities and infrastructure, provide the allocation of funds for the prevention and handling of traffic accidents as well as the obligation to carry out routine and or routine maintenance activities on roads and make efforts in preventing motor vehicle accidents due to damage roads by marking or signs and lighting to indicate the location of damaged / perforated roads.Keywords: Government Responsibility, Road Damage, Motor Vehicle Accidents